The Plant Stem A Microscopic Aspect - Schweingruber, Fritz H. (Springer International Publishing, 2018)
This unique and attractive open access textbook combines the beauty of macroscopic pictures of plant stems with the corresponding colorfully stained images of anatomical micro-structures. In contrast to most botanical textbooks, it presents all the stem characteristics as photographs and shows the microscopic reality. The amount of text is reduced to a minimum, and the scientific information is highlighted with short legends and labeled photographs, allowing readers to focus on the pictures to easily understand how the anatomical structures relate to genetic, ecological, decomposition and technical influences. It includes a chapter devoted to simple anatomical preparation techniques, and further chapters showing the cell content, cell walls, meristematic tissues and stem structures of all major taxonomic units and morphological growth forms in various ecological and climatic regions from subarctic to equatorial latitudes, as well as structures of fossil, subfossil and technically altered wood. This textbook appeals to students and researchers in the fields of plant anatomy, taxonomy, ecology, dendrochronology, history, plant pathology, and evolutionary biology as well as to technologists.